Domestic violence in emergency medicine patients. Issue 1 (20th January 2004) - Boyle, A; Robinson, S; Atkinson, P
Abstract : Domestic violence is an important public health issue. This review seeks to inform doctors who care for patients who have suffered domestic violence.